Ego depletion interferes with rule-defined category learning but not non-rule-defined category learning - Minda, John P.; Rabi, Rahel (Frontiers in Psychology, 2015)
Considerable research on category learning has suggested that many cognitive and environmental factors can have a differential effect on the learning of rule-defined categories as opposed to the learning of non-rule-defined categories. Prior research has also suggested that ego depletion can temporarily reduce the capacity for executive functioning and cognitive flexibility. The present study examined whether temporarily reducing participants’ executive functioning via a resource depletion manipulation would differentially impact rule-defined and non-rule-defined category learning. Participants were either asked to write a story with no restrictions (the control condition), or without using two common letters (the ego depletion condition). Participants were then asked to learn either a set of rule-defined categories or a set of non-rule-defined categories. Resource depleted participants performed more poorly than controls on the rule-defined task, but did not differ from controls on the non-rule-defined task, suggesting that self regulatory resources are required for successful rule-defined category learning. These results lend support to multiple systems theories and clarify the role of self-regulatory resources within this theory.